Balloon atrial septostomy under two dimensional echocardiographic control. Issue 1 (January 1982) - Allan, L D; Leanage, R; Wainwright, R; Joseph, M C; Tynan, M
Abstract : Two dimensional echocardiography has been used to guide balloon atrial septostomy in five cases of transposition of the great arteries. A single lumen balloon catheter was used. The catheter can be accurately located within the left atrium before inflation of the balloon, thus avoiding some of the traumatic accidents possible during septostomy. The balloon can be observed creating the atrial defect and the approximate size of the resulting defect noted. It can also be seen if the foramen ovale is only being stretched and not torn. The use of the two dimensional echocardiogram during septostomy should significantly contribute to the speed, efficiency, and safety of the procedure.